2015
DOI: 10.1007/s11356-015-4073-y
|View full text |Cite
|
Sign up to set email alerts
|

Metal uptake via phosphate fertilizer and city sewage in cereal and legume crops in Pakistan

Abstract: Crop irrigation with heavy metal-contaminated effluents is increasingly common worldwide and necessitates management strategies for safe crop production on contaminated soils. This field study examined the phytoavailability of three metals (Cd, Cu, and Zn) in two cereal (wheat, maize) and legume (chickpea, mungbean) crops in response to the application of either phosphatic fertilizer or sewage-derived water irrigation over two successive years. Five fertilizer treatments, i.e. control, recommended nitrogen (N)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 81 publications
(28 citation statements)
references
References 22 publications
1
25
0
1
Order By: Relevance
“…It has been studied that P application to the soil decreases the phytoavailability of Cd from contaminated soil . Application of half the recommended dose of P, as practiced by farmers, seems to be an economical option for the production of cereal and legume crops on sewage effluent irrigated soils …”
Section: Bioavailability Of Ptes In Contaminated Soilsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been studied that P application to the soil decreases the phytoavailability of Cd from contaminated soil . Application of half the recommended dose of P, as practiced by farmers, seems to be an economical option for the production of cereal and legume crops on sewage effluent irrigated soils …”
Section: Bioavailability Of Ptes In Contaminated Soilsmentioning
confidence: 99%
“…The Cd content of P fertilizers varies depending upon the source of the raw rock phosphate used in its manufacturing process. Murtaza et al reported that application of P fertilizer reduced soil solution Cd and its mobility by precipitating the Cd in the low solubility products such as Cd 3 (PO 4 ) 2 , Cd 2 PO 3 , CdCO 3 , or Cd(OH) 2 which tend to be recalcitrant and generally unavailable to cereals (wheat, maize) and legumes (chickpea, mung bean). The reduction of Cd in plant tissues may be due to P‐induced sorption of Cd in the soil .…”
Section: Bioavailability Of Ptes In Contaminated Soilsmentioning
confidence: 99%
See 3 more Smart Citations